Heat transfer in adjacent interacting impinging synthetic jets - MURRAY, DARINA; PERSOONS, TIM (ASME, 2009)
An impinging synthetic jet can attain heat transfer rates comparable to a continuous jet, without net mass input. However it needs a forced cross-flow to supply fresh cooling medium. The vectoring effect of adjacent synthetic jets allows directing the flow by changing the phase between the jets. This study uses the vectoring effect of two adjacent synthetic jets to draw in fresh air, while maintaining high impingement cooling performance. The experimental approach applies infrared thermography and particle image velocimetry to quantify the local convective heat transfer and flow field, respectively. The heat transfer profiles for various phase differences have been compared to the mean flow field and wall-normal velocity fluctuation intensity. For a fixed operating point (stroke length and Reynolds number) and geometry, the cooling performance has been optimised for phase and jet-to-surface spacing, resulting in about 90% enhancement of the maximum and overall cooling rate compared to a single jet, without the need for external cross-flow forcing.
ASME Summer Heat Transfer Conference
PUBLISHED
paper HT2009-88440
San Francisco, USA
Keywords: mechanical engineering; particle image velocimetry; synthetic jets; Smart & Sustainable Planet; Telecommunications